Fuzzy adaptive fault-tolerant control for an unmanned surface vehicle with prescribed tracking performance - Bao, Yunuo; Gao, Ji; Peng, Peng (Frontiers in robotics and AI, 2025)
Unmanned surface vehicles (USVs), as a type of marine robotic systems, are widely used in various applications such as maritime surveillance, environmental monitoring, and cargo transportation. This article addresses the trajectory tracking control issue for an USV subject to model uncertainties and actuator faults. A logarithm barrier Lyapunov functions based predefined tracking control scheme is proposed to regulate the position error of the USV into predefined performance region. Then, to ensure the predefined transient and steady state tracking performance of the USV in the presence of actuator faults, we propose an adaptive fuzzy fault-tolerant controller to address the actuator faults. Additionally, to deal with the uncertainties arising from the USV system model, fuzzy logic systems are utilized to estimate the unknown hydrodynamic parameters. Based on the Lyapunov stability criterion, it can be demonstrated that all the closed-loop signals are bounded. Finally, the validity of the developed control scheme is demonstrated from simulation results.